2006
DOI: 10.1002/app.25193
|View full text |Cite
|
Sign up to set email alerts
|

Ageing of soft thermoplastic starch with high glycerol content

Abstract: In this study, a soft and thermoplastic starch with an improved ageing-resistant property was prepared by melt blending method for a biodegradable biomaterial. The glycerol content varies from 30 to 60 wt %. The aging temperature and humidity of the glycerol-plasticized thermoplastic starch (GTPS) was 378C and 50 6 5 RH %, respectively. The retrogradation was characterized by X-ray diffraction (XRD), dynamic mechanical thermal analysis (DMTA), Fourier transform infrared (FTIR), and the stressstrain mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 36 publications
(51 reference statements)
5
53
0
6
Order By: Relevance
“…3b), the A-type crystallization peaks disappeared, only two weak crystallization peaks were detected at 2Â = 14 • and 21 • which were the characteristic peaks of V-type [30]. Besides, an amorphous dispersion band was found at 2Â = 19 • [31].…”
Section: The Xrd Analysis Of Tpsmentioning
confidence: 91%
“…3b), the A-type crystallization peaks disappeared, only two weak crystallization peaks were detected at 2Â = 14 • and 21 • which were the characteristic peaks of V-type [30]. Besides, an amorphous dispersion band was found at 2Â = 19 • [31].…”
Section: The Xrd Analysis Of Tpsmentioning
confidence: 91%
“…The presentation of peak 2θ at 17 o and 20 o implied the formation of double-helical B-type crystalline. The peak at 2θ=20 o corresponded to the single helical crystal structure of V-type, which indicated the formation of amylose-glycerol complexes during processing [17]. The crystallinity of fresh film increased slightly with the increasing of glycerol content.…”
Section: -3mentioning
confidence: 96%
“…Citric acid is proven to be a crystallization inhibitor for starch, because of esterification and strong hydrogen bonding interactions with starch. 13,46 Different plasticizer amounts of malic acid displayed no significant differences in retrogradation after 56 days at RH100%. Research of Yu et al 13 showed that citric acid quantities of 3 wt % were enough for suppressing starch recrystallization for 70 days at 100% relative humidity.…”
Section: Articlementioning
confidence: 96%
“…Peaks in the range 1721-1750 cm 21 have been reported for esterification of starch and cellulose samples. [40][41][42][43][44][45][46] Although absorption signals near 1720 cm 21 may also be ascribed to carboxylic acid groups in di-acidic molecules present in the sample. 6 Increased absorption in the range 1200-1300 cm 21 was attributed to C-O stretching in esters.…”
Section: Ft-ir Analysesmentioning
confidence: 99%